Collection and manufacturing procedures in contemporary painting: interview with Silvia Carvalho (Palíndromo, 2023)
Artist Silvia Carvalho (Florianópolis-SC) collects and manufactures earth pigments, creating transformative rituals. Her work in painting demonstrates the relevance of the investigation, as it explores procedures that precede the painting itself. In this interview, Silvia Carvalho invites us to take a tour in her studio and her creative processes, especially the collect, manufacture and uses of earthy pigments, highlighting the relationship between art and life.
Keywords: interview; contemporary painting; procedures; earthy pigments; creative process